THE ROLE OF THE ASEAN HUMAN RIGHTS INSTITUTIONS TO MANAGE RELIGION-BASED CONFLICT IN SOUTHEAST ASIA COUNTRIES - Heribertus Jaka Triyana, Heribertus Jaka Triyana (2014)
This article aims to describe and critically examine the ASEAN human rights norms and mechanism as the agreement of common local wisdoms to remedy and to redress religion based conflicts in South East Asian countries which mounting binding legal righteous and entitlement. Further, it tries to focus on its norms and mechanisms to advocate and to adjudicate role and function of the human rights norms and mechanisms for better protection of human rights and fundamental freedoms in particular attention to manage religion based conflicts. This article will elaborate with three theory: theory of complementarity, theory of social function of law and theory of state sovereignty. It reveals that these tremendous influence for better human rights advocacy at strategic level within ASEAN cooperation while at the operational and tactical levels, it has less attention to religion based conflicts. Keywords: human rights, religion based of conflict.